2020
DOI: 10.1109/tvt.2020.2979918
|View full text |Cite
|
Sign up to set email alerts
|

Reinforcement Learning Based Cooperative Coded Caching Under Dynamic Popularities in Ultra-Dense Networks

Abstract: For ultra-dense networks with wireless backhaul, caching strategy at small base stations (SBSs), usually with limited storage, is critical to meet massive high data rate requests. Since the content popularity profile varies with time in an unknown way, we exploit reinforcement learning (RL) to design a cooperative caching strategy with maximum-distance separable (MDS) coding. We model the MDS coding based cooperative caching as a Markov decision process to capture the popularity dynamics and maximize the long-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(27 citation statements)
references
References 45 publications
0
27
0
Order By: Relevance
“…The coded cooperation of cache-enabled IAB nodes was considered in (Gao et al, 2020) and (Vu et al, 2018). The authors in (Vu et al, 2018) studied the energy-efficiency performance of a cache-enabled IAB network, with the consideration of the cache capability.…”
Section: Caching Strategy Designmentioning
confidence: 99%
See 2 more Smart Citations
“…The coded cooperation of cache-enabled IAB nodes was considered in (Gao et al, 2020) and (Vu et al, 2018). The authors in (Vu et al, 2018) studied the energy-efficiency performance of a cache-enabled IAB network, with the consideration of the cache capability.…”
Section: Caching Strategy Designmentioning
confidence: 99%
“…Simulation results showed that uncoded caching outperforms coded caching in the small user cache size regime, while coded caching outperforms uncoded caching in the small BSs cache size regime. In (Gao et al, 2020), the authors applied the maximum distance separable (MDS) code at the IAB nodes. By leveraging the Q-learning model, the content caching decision is derived.…”
Section: Caching Strategy Designmentioning
confidence: 99%
See 1 more Smart Citation
“…A DQN is proposed for finding a suboptimal solution. Though Reference [89] is regarded as solving what to cache problem, like Reference [79][80][81][82][83][84][85][86][87][88]102], the reinforcement learning approach plays a different role. In Reference [89], a DNN is utilized for content popularity prediction and then an RL is used for DNN hyperparameters tuning instead of determining caching content.…”
Section: Drlmentioning
confidence: 99%
“…Reference [93] provides a DDPG model to cope with continuous valued control decision for 3C in vehicular edge networks. The work in Reference [102] focuses on the cooperative caching policy at FBSs with maximum distance separable coding in ultra dense networks. A Q-learning model is utilized to determine caching categories and the content quantity at FBSs during the off-peak duration.…”
Section: Drlmentioning
confidence: 99%